Carbon dioxide sequestration through steel slag carbonation: Review of mechanisms, process parameters, and cleaner upcycling pathways - Christopher DiGiovanni; Ousmane A. Hisseine; Adedapo Noah Awolayo (Journal of CO2 Utilization, 2024)
The direct carbonation of steel slag has emerged as a promising approach for carbon dioxide (CO2) utilization and sequestration, holding potential for advancing sustainable steel production. Despite considerably high expectations for these cleaner upcycling pathways, their maturity level remains relatively low and large-scale direct carbonation of steel slag is largely untested. To facilitate steel slag carbonation on a scale necessary for a zero-carbon future economy, this article provides a comprehensive review of fundamental carbonation mechanisms and critical parameters governing the reaction process, including temperature, pressure, reaction time, liquid-to-solid ratio, and CO2 partial pressure. The study critically examines the unique interactions among these process parameters, which can either limit or enhance the process optimization. The spectrum of scientific challenges associated with this pathway, including reaction rate limitations and the carbonated product valorization, particularly as a binder or aggregate in the construction sector, are identified and addressed. These insights aim to enhance the carbonation potential of steel slag for possible cleaner upcycling implementation pathways, ultimately facilitating the development of more efficient and sustainable carbon capture utilization and sequestration (CCUS) technologies. The proposed improvements are expected to be instrumental in promoting sustainable practices, not only to foster the decarbonization of the steelmaking industry but also in aiding other hard-to-abate sectors, such as the cement and concrete industry, in achieving their own decarbonization goals.